2012
DOI: 10.1088/2043-6262/3/3/035002
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and anti-cancer activity of polymer-encapsulated curcumin nanoparticles

Abstract: Curcumin (Cur) is a yellow compound isolated from rhizome of the herb curcuma longa. Curcumin possesses antioxidant, anti-inflammatory, anti-carcinogenic and antimicrobial properties, and suppresses proliferation of many tumor cells. However, the clinical application of curcumin in cancer treatment is considerably limited due to its serious poor delivery characteristics. In order to increase the hydrophilicity and drug delivery capability, we encapsulated curcumin into copolymer PLA-TPGS, 1,3-beta-glucan (Glu)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Antitumor Activity Ha et al [82] developed water soluble copolymer Cur-PLA-TPGS-, Cur-Gl-, Cur-OCMCS-, and Cur-OCMCS-Fol-encapsulated curcumin nanoparticles and found that these nanoparticles could be used in cancer therapy. Pan et al [83] evaluated the antitumor effects of the curcumin analogue GL63 on radioresistant nasopharyngeal carcinoma (NPC) CNE2R cells and parental CNE2 cells.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Antitumor Activity Ha et al [82] developed water soluble copolymer Cur-PLA-TPGS-, Cur-Gl-, Cur-OCMCS-, and Cur-OCMCS-Fol-encapsulated curcumin nanoparticles and found that these nanoparticles could be used in cancer therapy. Pan et al [83] evaluated the antitumor effects of the curcumin analogue GL63 on radioresistant nasopharyngeal carcinoma (NPC) CNE2R cells and parental CNE2 cells.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Among the various transition metal oxides, MnO 2 is one of the most studied active materials for pseudo-capacitors because of its low cost, high positive electrode potential and relatively low molecular weight. 33,34 However, the poor stability presented after just a few charge-discharge cycles is a crucial limitation for practical application of MnO 2 . Moreover, the electrochemical and catalysis properties of MnO 2 are strongly dependent on its dimensions, morphology and crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their small size and mobility, nanoparticles have higher cell uptake when compared to microparticles and are available to a wider range of cellular and intracellular targets. Ha et al reported the use of fluorescence images to study the cellular uptake of a polymer encapsulated curcumin nanoparticles and suggested that the absorption of curcumin takes place into the cells instead of adhesion to the surface as indicated by their distribution in the nuclear zone. In a study by Yuan and Zheng the fluorescence intensity was more in HepG2 cells treated with curcumin incorporated glycyrrhetic acid modified pullulan nanoparticles compared to those treated with native curcumin.…”
Section: Resultsmentioning
confidence: 99%